Land, Chiefs, Mining : South Africa's North West Province since 1840 - Manson, Andrew; Mbenga, Bernard (Book collections on Project MUSE., 2014)
"Land, Chiefs, Mining, explores aspects of the experience of the Batswana in the thornveld and bushveld regions of the North-West Province, shedding light on defining issues, moments and individuals in this lesser known region of South Africa. Some of the focuses are: an important Tswana kgosi (chief), Moiloa 11 of the Bahurutshe ; responses to and participation in the South African War and its aftermath, 1899-1907; land acquisition ; economic and political conditions in the reserves ; resistance to Mangope's Bophuthatswana; the impact of game parks and the Sun City resort; rural resistance and the liberation struggle; and African reaction to the platinum mining revolution."--Publisher: http://witspress.co.za/catalogue/land-chiefs-mining